2018
DOI: 10.7570/jomes.2018.27.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia in Obese Children and Adolescents

Abstract: The increasing prevalence of obesity in children and adolescents is a serious public health concern. Hypertriglyceridemia is common in obese children and adolescents, and elevated triglyceride (TG) level is a known biomarker of cardiometabolic risk. Results from genetic studies suggest that TG and TG-rich lipoproteins and, more specifically, remnant cholesterol are in the causal pathway of cardiovascular disease. However, simultaneous measurement of all remnants has not yet been established, and plasma TG leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
(59 reference statements)
2
18
0
1
Order By: Relevance
“…On the other hand, elevated TG levels were reported more commonly in participants with high WHtR (> 0.5) or in abdominally obese participants who might be more at risk of cardiovascular disease in the future. These results were also supported by other studies [24,25,26]. In addition, our previous study reported that a child's nutritional status was positively correlated with blood pressure.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, elevated TG levels were reported more commonly in participants with high WHtR (> 0.5) or in abdominally obese participants who might be more at risk of cardiovascular disease in the future. These results were also supported by other studies [24,25,26]. In addition, our previous study reported that a child's nutritional status was positively correlated with blood pressure.…”
Section: Discussionsupporting
confidence: 90%
“…As universally acknowledged, lipid metabolism, especially triglyceride (TG) metabolism plays a central role in Mets pathogenesis [ 11 ]. TG elevation is one of the components of Mets and a risk factor for abdominal obesity [ 12 ], and the synthesis of TG is associated with glucose metabolism through the tricarboxylic acid cycle [ 13 ]. Consequently, the gene locus featured by TG regulation is expected to become the target of Mets gene-directed therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As insulin is critical for cellular glucose uptake and to prevent efflux of fat from the adipose tissue, also known as lipolysis inhibition, children with insulin resistance are at risk of developing type 2 diabetes and cardiovascular complications at an earlier age. HOMA-IR (homeostatic model assessment of insulin resistance) and triglycerides to HDLC ratio (TGHDL) are valid clinical surrogates of insulin resistance and are predictors of metabolic syndrome and cardiovascular risks in children [ 12 , 13 ]. In children, high levels of leptin and insulin are often associated with low levels of adiponectin and high levels of resistin, as obesity is a condition that modulates the secretion of both adipokines, which exacerbates insulin resistance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%